STRATEGI KOMUNIKASI PENGEMBANGAN KAMPUNG WISATA JODIPAN DAN KAMPUNG TOPENG KOTA MALANG - Novan Andrianto; Achmad Yanu Alif Fianto (Universitas Baturaja, 2022)
The purpose of this study was conducted as an effort to identify the advantages of tourism in Jodipan Tourism Village and Malang City Topeng Village. The identification of these advantages can then be used as a basis in formulating a communication strategy for the development of a strategic plan from“Jodipan Tourism Village and Mask Village” Malang City e. The strategy is formulated based on the local superior sectors and the uniqueness of the community's social environment. This study utilizes a participatory approach and uses qualitative data analysis techniques. In the formulation of a communication strategy for the development of “Jodipan Tourism Village and Mask Village” Malang City, a situation analysis and descriptive analysis were used. The results of the analysis in this study can reveal the various potentials possessed by “Jodipan Tourism Village and Mask Village” Malang City both externally and internally which can be further developed. Strategies that can be applied are emphasized on developing the theme of the Tourism Village which has a unique cultural arts perspective with strong characteristics and is based on the social strength of the community.